Impacts of Microplastics on the Cells of Aquatic Organisms - Keke, Adolfin; Naring, Theresia; Itu, Maria Dolfiana; Wae, Veronika P. Sinta Mbia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Microplastics (<5mm) are currently one of the most concerning contaminants in aquatic environments, especially in coastal areas of Indonesia. This literature review aims to identify the types, sources, and abundance levels of microplastics, as well as their potential impacts on aquatic organisms and implications for human health. Microplastics were found at concentrations of approximately 38,000 particles per kilogram of sediment in Indonesian waters and more than 1,500 particles per individual in aquatic animals. Microplastic pollution has been shown to accumulate in the digestive systems of organisms and can translocate to tissues, which can then enter the human food chain. Health impacts that have been identified include the risk of chronic inflammation, digestive system disorders, liver damage, and an increased risk of cancer. Overall, this literature review shows that microplastic pollution in aquatic organisms in Indonesia is at a very worrying level and requires decisive action through reducing the use of plastic materials, improving waste processing, and continuous monitoring. These conditions can harm all aquatic organisms, leading to digestive disorders and even death.